Evaluating Yourself and Your Peers - Mingye Ma; Gerhard Riener; Youzong Xu (Institute of Labor Economics (IZA), 2024)
We explore the role of self- and peer evaluations in education, with a particular emphasis on gender differences. We construct a model of (self-)deception to predict outcomes for scenarios with and without self-evaluation. By using unique data from a first-year economics class at a Sino-UK university, we examine how students assess their own and their peers' contributions to group projects under varying self-assessment conditions. Our findings reveal a significant self-serving bias across both genders, though with subtle distinctions. Women, despite greater societal recognition, exhibit smaller self-social evaluation gaps (SSEG). The variation in abstention rates between treatments is mainly attributed to lowerperforming males. These findings indicate that the possibility of self-assessment influences rating behavior, potentially exacerbating gender disparities and affecting gender equity.
Keywords: D01; D91; I23; C93; 330; higher education; incentives; field experiment; peer evaluation; gender